Epizoic amoebae from the gills of turbot Scophthalmus maximus - Dyková, Iva; Figueras Huerta, Antonio; Novoa, Beatriz (Diseases of Aquatic Organisms, 1999)
6 páginas, 30 figuras Species of amoebae belonging to the genera Platyamoeba Page, 1969, Vannella Bovee, 1965 and Flabellula Schaeffer, 1926 were found to accompany Paramoeba sp., the agent of amoebic gill disease (AGD),in cl~nicallyd iseased turbots. The same community of epizoic gymnamoebae was found on the gills of turbots which revealed no gill abnormalities but slight behavioral signs indicat~veof suboptimal health status. The assemblage of the above-mentioned free-living amoebae capable of colonizing tissue of turbots was supplemented with species recognized in samples fixed from primary isolates for transmission electron microscopy. The pathogenic potential of epizoic gill amoebae in turbots is discussed gill tissue of turbots was supplemented with species recognized in samples fixed from primary isolates for transmission electron microscopy. The pathogenic potential of epizoic gill amoebae in turbots is discussed. Grant Agency of the Academy of Sciences of the Czech Republic Peer reviewed